Insomnia is associated with quality of life impairment in medical-surgical intensive care unit survivors - Parsons, Elizabeth C.; Hough, Catherine L.; Vitiello, Michael V.; Zatzick, Douglas; Davydow, Dimitry S. (Heart & lung, 2015)
To examine the prevalence of insomnia and its relationship to health-related quality of life (HRQOL) post-intensive care unit (ICU). The burden of post-ICU insomnia is unknown. This cross-sectional study examined data from 120 patients with an ICU stay >24 h. Pre-hospital health was assessed in-hospital. Insomnia, HRQOL and post-ICU psychiatric symptoms were assessed at 12 months post-ICU. Over one-quarter (28%) of subjects met insomnia criteria at 12 months post-ICU. Post-ICU insomnia was independently associated with worse mental HRQOL (P < 0.01), as well as worse scores on the HRQOL sub-domains of bodily pain (P < 0.001), vitality (P < 0.05) and physical function (P < 0.05). However, these associations were no longer significant after adjusting for post-ICU psychiatric symptoms (P = 0.33). Insomnia is common among ICU survivors. Post-ICU insomnia is significantly associated with mental HRQOL and could identify ICU survivors who may benefit from further psychiatric evaluation. •In this medical-surgical cohort, 28% of 1-year survivors endorsed post-ICU insomnia.•Post-ICU insomnia was linked to in-hospital acute stress and opioid exposure.•Post-ICU insomnia was linked to post-hospital depression, PTSD, and pain.•Insomnia may identify ICU survivors who merit evaluation for psychiatric disorders.